2016
DOI: 10.1155/2016/5025174
|View full text |Cite
|
Sign up to set email alerts
|

Are “Theory of Mind” Skills in People with Epilepsy Related to How Stigmatised They Feel? An Exploratory Study

Abstract: Feelings of stigma are one of the main burdens reported by people with epilepsy (PWE). Adults with temporal or frontal lobe epilepsy and children with idiopathic generalised epilepsy are at risk of Theory of Mind (ToM) deficits. ToM refers to social cognitive skills, including the ability to understand the thoughts, intentions, beliefs, and emotions of others. It has been proffered that ToM deficits may contribute to the feelings of stigma experienced by PWE. In this study we tested this for the first time. We… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 47 publications
0
6
0
1
Order By: Relevance
“…Furthermore, social support was found to significantly predict lower stigma even when other sociodemographic variables had been taken into account in regression analyses [36]. To ascertain whether participants' social cognitive skills and their ability to understand the thoughts, intentions, beliefs, and emotions of others contributed to feelings of stigma, Noble, Robinson, and Marson compared "theory of mind" and stigma measures using regression analyses [50]; these were found to share little variance, regardless of participant seizure status, indicating that the model has little utility in understanding epilepsy stigma.…”
Section: Relational Factorsmentioning
confidence: 99%
“…Furthermore, social support was found to significantly predict lower stigma even when other sociodemographic variables had been taken into account in regression analyses [36]. To ascertain whether participants' social cognitive skills and their ability to understand the thoughts, intentions, beliefs, and emotions of others contributed to feelings of stigma, Noble, Robinson, and Marson compared "theory of mind" and stigma measures using regression analyses [50]; these were found to share little variance, regardless of participant seizure status, indicating that the model has little utility in understanding epilepsy stigma.…”
Section: Relational Factorsmentioning
confidence: 99%
“…It was designed to address wider questions regarding perceptions of stigma 9, 10. Participants were recruited by advertisements in the newsletters and websites of epilepsy interest groups and organizations within England, Scotland, Wales and the Republic of Ireland.…”
Section: Methodsmentioning
confidence: 99%
“…Only two studies have addressed the question of how social cognition specifically impacts on social functioning in patients with epilepsy [25,26]. The first study [25] investigated 67 patients with TLE and 30 healthy controls.…”
Section: Social Cognition and Social Functioning In Patients With Epimentioning
confidence: 99%
“…Although both FPT and GSI scores had significant and independent predictive effects on SOFSE subscales, only FPR predicted all six sub-scale scores. The authors of this study, therefore, concluded that social cognition A second study of over 500 epilepsy patients, tested the hypothesis that social stigma reported by patients with epilepsy is caused by ToM deficits [26]. Data was acquired remotely using online questionnaires.…”
Section: Social Cognition and Social Functioning In Patients With Epimentioning
confidence: 99%